2021
DOI: 10.4103/ijo.ijo_612_21
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of combined treatments in patients with retinal arterial macroaneurysm

Abstract: Purpose: To evaluate the outcome of the combined approach between intravitreal ranibizumab (IVR) and focal laser photocoagulation (FLP) in the treatment of symptomatic retinal arterial macroaneurysm (RAM). Methods: A total of 10 patients were included in this clinical case series report. They were diagnosed with symptomatic RAM (one eye in each) and assessed by a comprehensive ophthalmologic examination, including fluorescein angiography (FA), optical coherence tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…A study reported that combined treatment of laser and anti-VEGF could improve VA of symptomatic RAM [22] . However, in our study, patients in the combination group did not receive both laser and anti-VEGF treatments at the same time or within a short period; instead, the other treatment was added when the effect of the initial monotherapy failed to meet expectations.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that combined treatment of laser and anti-VEGF could improve VA of symptomatic RAM [22] . However, in our study, patients in the combination group did not receive both laser and anti-VEGF treatments at the same time or within a short period; instead, the other treatment was added when the effect of the initial monotherapy failed to meet expectations.…”
Section: Discussionmentioning
confidence: 99%
“…RAM is usually asymptomatic and resolves spontaneously in most cases. However, when hemorrhage and/or exudation affect the macula, severe vision loss occurs despite aggressive treatments including photocoagulation, vitrectomy, or antivascular endothelial growth factor intravitreal injections [3][4][5] . The main pathophysiology of RAM involves weakness of the vascular wall owing to aging and arteriosclerosis, which makes it more susceptible to the increased hydrostatic pressure seen in hypertension, leading to the dilatation of a major retinal arteriole [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%